2019
DOI: 10.1177/1756284819867839
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome is a risk factor for colorectal adenoma and cancer: a study in a White population using the harmonized criteria

Abstract: Background: Metabolic syndrome (MetS) has been associated with colorectal adenomas and cancer. However, MetS definitions have changed over time, leading to a heterogeneity of patients included in previous studies and a substantial inextensibility of observations across time or eastern and western populations. Our aim was to evaluate the association of ‘harmonized’ criteria-defined MetS and its individual components with colorectal neoplasia and cancer in a western population. Methods: In this multicenter, cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 61 publications
3
15
0
4
Order By: Relevance
“…Basic information concerning the eligible studies are listed in Tables 1 and 2. From 2006 to 2019, a total of 10 prospective cohort studies [18-21, 25, 34-38], 6 case-control studies [39][40][41][42][43][44], one retrospective cohort study [22] and one cross-sectional study [45] were included in the meta-analysis of CRC incidence, and 8 prospective cohort studies [25][26][27][46][47][48][49], 2 retrospective cohort study [50,51] and 3 case-control studies [52][53][54] were included in the meta-analysis for CRC mortality. Thirteen studies were conducted in Asia [21,22,27,37,38,42,43,46,48,[50][51][52]54], eight were performed in Europe [20, 25, 34, 39-41, 44, 45], and the remaining studies were executed in the USA [18,19,26,35,36,47,49].…”
Section: Literature Search and Study Characteristicsmentioning
confidence: 99%
“…Basic information concerning the eligible studies are listed in Tables 1 and 2. From 2006 to 2019, a total of 10 prospective cohort studies [18-21, 25, 34-38], 6 case-control studies [39][40][41][42][43][44], one retrospective cohort study [22] and one cross-sectional study [45] were included in the meta-analysis of CRC incidence, and 8 prospective cohort studies [25][26][27][46][47][48][49], 2 retrospective cohort study [50,51] and 3 case-control studies [52][53][54] were included in the meta-analysis for CRC mortality. Thirteen studies were conducted in Asia [21,22,27,37,38,42,43,46,48,[50][51][52]54], eight were performed in Europe [20, 25, 34, 39-41, 44, 45], and the remaining studies were executed in the USA [18,19,26,35,36,47,49].…”
Section: Literature Search and Study Characteristicsmentioning
confidence: 99%
“…This added to a survival rate of 10% after 5 years [5], and a limited treatment success with surgery or with 5-fluorouracil (5FU) combined with other agents, such as irinotecan, capecitabine or oxaliplatin, and monoclonal antibodies such as cetuximab and bevacizumab [6], emphasize the need to develop new effective strategies with therapeutic action. In recent years, a new approach for the prevention of the disease has been developed, acting on factors that increase the risk of this pathology, such as obesity and diabetes [7]. In this context, diet modulation has been suggested as a way of prevention/management against this type of tumor [8], even in combination with other cancer drugs such as 5FU [9].…”
Section: Introductionmentioning
confidence: 99%
“…Also, our results were consistent with Harlid et al, (19) who found no significant difference between cases and controls regarding weight, height and BMI. In the study conducted by Milano et al, (20) there was highly statistically significant differences between Positive and negative colonoscopy patients regarding Waist circum- ference and BMI (p<0.001). Also, Stocks et al, (21) found that, the use of BMI as a measure of obesity is hampered by the finding that BMI is not a specific measure of abdominal fat mass, which is linked to metabolic aberrations, such as insulin resistance (22).…”
Section: Discussion Discussionmentioning
confidence: 84%